Clinical Pharmacy 2016
DOI: 10.1136/ejhpharm-2016-000875.108
|View full text |Cite
|
Sign up to set email alerts
|

CP-108 Biosimilars: What do clinicians actually think?

Abstract: BackgroundThe expiry of patents for infliximab in Europe coincides with the arrival on the market of new biosimilars with potential savings. However, many clinicians are reluctant to consider biosimilars as a treatment option for their patients.PurposeThe aim of this study was to evaluate concerns raised about biosimilars in the medical community in our hospital in order to reference infliximab biosimilars.Material and methodsA questionnaire with different items was put online: knowledge about the regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Twenty surveys met the inclusion criteria and were included in this systematic review ( Figure 1). The included studies originated from the United States of America [15][16][17] , Belgium 18,19 , France [20][21][22] , Germany 23,24 , Italy 25 , Ireland 26 , Malta 27 , Hungary 28 , and the United Kingdom (UK) 29 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty surveys met the inclusion criteria and were included in this systematic review ( Figure 1). The included studies originated from the United States of America [15][16][17] , Belgium 18,19 , France [20][21][22] , Germany 23,24 , Italy 25 , Ireland 26 , Malta 27 , Hungary 28 , and the United Kingdom (UK) 29 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Only half of respondents had actually prescribed biosimilars at the time of the survey. 22 In Barsell et al 15 (U.S., 2017), 62% of dermatologists had a basic understanding of biosimilars, 27% reported a complete understanding, and 11% reported that they have never heard of biosimilars. Of those who reported having a complete understanding of biosimilars, 21% incorrectly described a biosimilar as a generic copy of a biologic molecule.…”
Section: Biosimilar Prescribing Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations